2018
DOI: 10.3389/fpls.2018.00942
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Moiety Enhancement by Overexpression of Geranyl(geranyl) Diphosphate Synthase and Geraniol Synthase Elevates Monomeric and Dimeric Monoterpene Indole Alkaloids in Transgenic Catharanthus roseus

Abstract: Catharanthus roseus is the sole source of two of the most important anticancer monoterpene indole alkaloids (MIAs), vinblastine and vincristine and their precursors, vindoline and catharanthine. The MIAs are produced from the condensation of precursors derived from indole and terpene secoiridoid pathways. It has been previously reported that the terpene moiety limits MIA biosynthesis in C. roseus. Here, to overcome this limitation and enhance MIAs levels in C. roseus, bifunctional geranyl(geranyl) diphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Moreover, Cluster-12,235.40340 was annotated to geranyl-geranyl diphosphate synthase 12 (GGPPS12). GGPPS is composed of an inactive small subunit and an active large subunit and generates important substrates associated with the biosynthesis of monoterpene compounds in various plants [35][36][37]. ZaTPS03 (Cluster-12,235.42010) was also identified in this study, which related to a typical monoterpene synthase that catalyses the transformation GPP into limonene as well as other related compounds [22].…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, Cluster-12,235.40340 was annotated to geranyl-geranyl diphosphate synthase 12 (GGPPS12). GGPPS is composed of an inactive small subunit and an active large subunit and generates important substrates associated with the biosynthesis of monoterpene compounds in various plants [35][36][37]. ZaTPS03 (Cluster-12,235.42010) was also identified in this study, which related to a typical monoterpene synthase that catalyses the transformation GPP into limonene as well as other related compounds [22].…”
Section: Discussionmentioning
confidence: 63%
“…The diverse chemical structures of the SMs determine their functions to the medicine and stress adaptation. Three major categories are (i) terpenes derived from mevalonic acid pathway [25] and methyl erythritol phosphate pathway [26], (ii) phenolics derived from malonic acid pathway or a few case shikimic acid pathway [27], (iii) N (Nitrogen) and S (Sulfur) containing compounds via tricarboxylic acid cycle or sometimes via shikimic acid pathway. Among the pathways of SMs accumulation, shikimic acid, mevalonic acid, phenylpropanoic acid and methyl erythritol phosphate pathways are highly regulated under stress stimuli.…”
Section: Generation and Diversity Of Secondary Metabolites In Plantsmentioning
confidence: 99%
“…In tomato fruits, co-expression of a noncatalytic small subunit of GPPS (GPPS-SSU) from snapdragon and ObGES from basil (Ocimum basilicum) enhanced the production of geraniol 6.9-and 19.2-fold compared to the ObGES and GPPS-SSU parental lines, respectively [258]. Similarly, in Catharanthus roseus, accumulation of secologanin, a geraniol derived-monoterpene indole alkaloid, was achieved upon overexpression of CrGES along with a bifunctional CrG(G)PPS [259,260]. In addition, a combinatorial production of geraniol in tobacco has been examined using different subcellular compartments (i.e., plastids, cytosol or mitochondria): results showed that plastid-targeted VoGES combined with expression GPPS from Picea abies (PaGDPS1) for GPP overproduction lead to the highest production of geraniol [261].…”
Section: Geraniol (C 10 H 18 O Monoterpenoid)mentioning
confidence: 99%